(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
The article discusses the issue of appositive and quasi-appositive repetition in English colloquial speech, comparing it with Russian. Based on the analysis of factual material, we can conclude that there is an isomorphism between these two types of relations, not only at the level of isolated or partial structures, where the relations are less strict, but also in larger combinations formed according to regular patterns. Additionally, the study emphasizes the functional relevance of appositive and quasi-appositive repetitions in communication, demonstrating that they contribute to the stylistic and pragmatic nuances of speech in addition to clarity and emphasis. English fiction from the 20th century was used in the study, and language was taken from a variety of Russian and English authors' works. Component, distributional, transformational, semantic field, contextual, and conceptual analyses were among the linguistic analytic techniques used in the study. Linguists and language learners can more accurately model colloquial language use and uncover subtle semantic and syntactic links by comprehending these patterns in both English and Russian. This finding, in our view, provides a strong argument for considering quasi-apposition as an analogue of real apposition, differing from it in the same way that its components do. Verbs, adjectives, and adverbs should be regarded as belonging to the category of quasi-appositions. The authors conclude that the study highlights the structural and functional relevance of quasi-appositions in colloquial speech by showing how they serve as systematic equivalents of appositions in English and Russian.